Streaming and Screen Culture in Asia-Pacific
XIV, 333 p.
Keywords: “This exciting new collection explores the dynamic terrain of streaming platforms in the Asia Pacific and the attendant transformation of screen cultures in the region. The perspectives offered are timely, engaging, and help us make sense of a vast and rapidly changing field.” — Olivia Khoo, Associate Professor in Film and Screen Studies, Monash University, Australia, author of Asian Cinema: A Regional View (2021) and co-editor of The Routledge Handbook of New Media in Asia (2016) This book is an interdisciplinary collection exploring the impact of emergent technologies on the production, distribution and reception of media content in the Asia-Pacific region. Exploring case studies from China, Japan, South Korea, India, Thailand and Australia, as well as American co-productions, this collection takes a Cultural Studies approach to the constantly evolving ways of accessing and interacting with visual content. The study of the social andtechnological impact of online on-demand services is a burgeoning field of investigation, dating back to the early-2010s. This project will be a valuable update to existing conversations, and a cornerstone for future discussions about topics such as online technologies, popular culture, soft power, and social media. Louisa Mitchell is an independent scholar and editor. Her doctoral thesis, “Disrupting Heritage Cinema: The Historical Films of South Korea,” was completed at the University of Leeds in 2019, under the WRoCAH Doctoral Research Partnership. Her research interests include national cinemas, colonialism/postcolonialism, and issues of cultural and historical representation. She has most recently been published in the 2021 collection Renegotiating Film Genres in East Asian Cinema and Beyond (2020) by Lin Feng and James Aston. Michael Samuel is a Lecturer in Film and Television Studies at the University of Bristol, UK. He is the author of Popular Factual Heritage Television (2022) and Northern Exposure: A Cultural History (2021), and the co-editor of True Detective: Critical Essays on the HBO Series (2017). He is currently editing an anthology about television and empathy.